Upaya Pendampingan Peningkatan Pengetahuan Keluarga Tentang Pencegahan Hipertensi Pad Masa Pandemi Covid-19 - Halimah, Nur; Salaman Alhidayat, Nurun; Zakariyati, Zakariyati; Esti Handayani, Dwi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
Hypertension is one of the non-communicable diseases that is an important health problem throughout the world because of its prevalence which continues to increase in 2019 to 22% in the age group 18 years, as well as its association with cardiovascular disease, stroke, retinopathy and kidney disease. The purpose of this mentoring is to increase family knowledge, especially in Barisallo Village, Kel. Parangloe Kab. Gowa. The method used is the lecture method using banner and lieflet media. This activity was carried out for 6 days. The results of the activities include the planning, implementation and evaluation stages. From the results of the service, there are still many people who experience a diagnosis/or problems with high blood pressure, and there are still many people who do not know how to prevent hypertension itself. So from this basis, community service is about efforts to increase public knowledge to reduce the risk of hypertension to coincide with the spread of covid 19. It is hoped that health workers will be even more active in conducting health education, especially in Barisallo Village, Kec. Parangloe.